2017
DOI: 10.1158/1078-0432.ccr-17-0120
|View full text |Cite
|
Sign up to set email alerts
|

Infiltrating T Cells Increase IDO1 Expression in Glioblastoma and Contribute to Decreased Patient Survival

Abstract: Purpose Indoleamine 2,3 dioxygenase 1 (IDO1) mediates potent immunosuppression in multiple preclinical models of cancer. However, the basis for elevated IDO1 expression in human cancer, including the most common primary malignant brain tumor in adults, glioblastoma (GBM), is poorly understood. The major objective of this study is to address this gap in our understanding of how IDO1 expression contributes to the biology of GBM, and whether its level of expression is a determinant of GBM patient outcome. Exper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
140
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 147 publications
(148 citation statements)
references
References 39 publications
7
140
1
Order By: Relevance
“…In the present study, we found that IDO1 expression was positively correlated with the expression of the inhibitory checkpoint molecules PD-L1, PD-L2, PD-1, and CTLA-4, as well as the infiltration of suppressive immune cells, including Tregs, TAMs, and MDSCs, in agreement with previous reports in various solid tumors [29][30][31][32][33][34]. Unexpectedly, the upregulation of IDO1 expression was positively correlated with an increased density of CD8 + TILs in PSCC, which may be related to a poor prognosis.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we found that IDO1 expression was positively correlated with the expression of the inhibitory checkpoint molecules PD-L1, PD-L2, PD-1, and CTLA-4, as well as the infiltration of suppressive immune cells, including Tregs, TAMs, and MDSCs, in agreement with previous reports in various solid tumors [29][30][31][32][33][34]. Unexpectedly, the upregulation of IDO1 expression was positively correlated with an increased density of CD8 + TILs in PSCC, which may be related to a poor prognosis.…”
Section: Discussionsupporting
confidence: 93%
“…Indole‐amine‐2,3‐dioxygenase (IDO) is responsible for the first enzymatic step of tryptophan catabolism by the kynurenine pathway performed as the rate‐limiting enzyme. Protein expression of IDO was found to be high in a number of tumor samples and contribute to decrease patient survival . IDO expression in various histologic cancer types seems to build an immune‐suppressive microenvironment by regulating immune cells such as T effector cells, Treg cells, and MDSC .…”
Section: Introductionmentioning
confidence: 99%
“…Protein expression of IDO was found to be high in a number of tumor samples and contribute to decrease patient survival. 3,4 IDO expression in various histologic cancer types seems to build an immune-suppressive microenvironment 5,6 by regulating immune cells such as T effector cells, 7 Treg cells, 8 and MDSC. 9,10 On the other hand, several studies have provided compelling evidence for pro-tumor functions of neutrophils by immune suppression.…”
Section: Introductionmentioning
confidence: 99%
“…Namely, tryptophan dioxygenase (TDO), as well as tryptophan hydroxylase 1 (TPH1) and TPH2, collectively possess the ability to convert Trp into downstream metabolites. Although TDO is highly expressed in a majority of patient-resected GBM [9,50] it’s considered to be an unlikely contributor to AMT uptake, based on the high specificity for unmodified L -Trp [51,52]. In contrast, AMT is readily converted by TPH enzyme [53], and while the expression levels for the serotonergic pathway catalysts are currently unknown in GBM, they are the subject of an ongoing investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The enzyme, indoleamine 2,3 dioxygenase (IDO1), is an attractive immunologic target for the treatment of GBM due to its high level of expression [9] and potently immunosuppressive activity [10]. IDO1 converts tryptophan (Trp) into kynurenine (Kyn), and depletion of Trp [11] or the accumulation of Kyn, have been demonstrated to suppress T cell effector functions and/or increase conversion of naïve CD4 + T cells into FoxP3 + regulatory T cells (Tregs) [12].…”
Section: Introductionmentioning
confidence: 99%